The sight / 1. - Clement-Davies, David, 1961- (Legend of the Sight, 2007)
Morgra, a lone wolf that possesses a mysterious and terrifying power known as the Sight, sets off a battle that involves all of nature when she attempts to find a pup, born into a brave and loving pack, that holds the key to a power that could control the world.